HYDROTHERAPY IN THE ELDERLY: BALANCE AND FUNCTIONALITY (CIPEEX, 2022)
HYDROTHERAPY IS A PHYSIOTHERAPY TECHNIQUE THAT USES THE EFFECTS OF WATER AS A THERAPEUTIC RESOURCE FOR THE PREVENTION AND REHABILITATION OF PATIENTS. IT BASICALLY CONSISTS OF THE PRACTICE OF EXERCISES IN THE POOL THAT, AT APPROPRIATE TEMPERATURES, AIM TO PROMOTE FUNCTIONAL GAINS, OFFERING A BETTER QUALITY OF LIFE FOR THE PATIENT. ITS THERAPEUTIC PURPOSES ARE DIRECTLY RELATED TO BALANCE STIMULATION, REDUCING THE RISK OF FALLS, GAIT STABILITY, PROMOTING THE EFFICIENT FUNCTIONING OF THE SOMATOSENSORY, VISUAL AND VESTIBULAR SYSTEMS. THE PRESENT STUDY AIMS TO EVALUATE THE FUNCTIONAL PERFORMANCE AND BALANCE IN THE ELDERLY WHO PRACTICE HYDROTHERAPY, IN ADDITION TO IDENTIFYING THEIR SOCIODEMOGRAPHIC PROFILE. THE METHODS USED TO CARRY OUT THIS ANALYSIS WERE THE 6-MINUTE WALK TESTS, THE BERG BALANCE SCALE AND A SOCIODEMOGRAPHIC QUESTIONNAIRE. THE STUDY IS OBSERVATIONAL, CROSS-SECTIONAL, ANALYTICAL-DESCRIPTIVE, MAKING IT POSSIBLE TO OBSERVE A FUNCTIONAL PERFORMANCE AND BALANCE OF THE ELDERLY PRACTITIONERS OF HYDROTHERAPY. THE MEAN AGE WAS 69.6 YEARS, 7 (87.5%) WERE WOMEN AND 1 (12.5%) WERE MEN. THE REFERENCE VALUES, MEAN AND STANDARD DEVIATION OF THE GROUP WERE RESPECTIVELY: GLOBAL BERG BALANCE SCALE SCORE (BETWEEN 41 - 56), (52.3), (6.9); DISTANCE COVERED IN THE 3RD MINUTE OF THE WALKING TEST (219.32M), (170.6M), (66.67M); DISTANCE COVERED AT THE END OF THE WALK TEST (438.64M), (262.1M), (83, 84M). THE RESULTS OBTAINED IN THE SOCIODEMOGRAPHIC QUESTIONNAIRE DEMONSTRATE THE IMPORTANCE OF PHYSICAL ACTIVITY IN THE ELDERLY POPULATION, BOTH TO PREVENT CHANGES IN BALANCE AND FUNCTIONALITY, AS WELL AS FOR PSYCHOLOGICAL AND SOCIAL WELL-BEING. FROM THE OBSERVATION OF THE ASPECTS RESEARCHED, IT IS CONSIDERED THAT THE RESULTS REACHED A GOOD AVERAGE IN THE PERFORMANCE OF THE ELDERLY WHO PRACTICE HYDROTHERAPY, BECAUSE EVEN NOT REACHING ALL THE PREDICTED VALUES, THEY REMAINED WITH A GOOD GLOBAL BERG SCORE AND WITHOUT INTERCURRENCES. WE CONCLUDE, THEREFORE, THAT HYDROTHERAPY IS BENEFICIAL FOR THE ELDERLY PATIENT, SIGNIFICANTLY IMPROVING THEIR PHYSICAL, MENTAL AND SOCIAL QUALITY OF LIFE.
Keywords: hidroterapia; fisioterapia; idosos; funcionalidade